If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(x+5)-6=4x-8
We move all terms to the left:
2(x+5)-6-(4x-8)=0
We multiply parentheses
2x-(4x-8)+10-6=0
We get rid of parentheses
2x-4x+8+10-6=0
We add all the numbers together, and all the variables
-2x+12=0
We move all terms containing x to the left, all other terms to the right
-2x=-12
x=-12/-2
x=+6
| -4/4=2/3z | | 8k=+28 | | -5-6a=-5(1-4a) | | 2x+1.4=5.8 | | 6x+4-8x-10=-24 | | 6(2x-4)+2x=3(x-4) | | 5(x+2)-8(x+2)=-3x-6 | | -21-8x=19-6x | | -44=m+4 | | |4x-|2x+1||=4 | | f(4)=-2(-5)+1/3 | | -45+4x=15+7x | | 5x-10+7x=2(5x-8) | | 1w-2.5=-1.4 | | 3(2x+3)=17+8x | | 2/3c-7c=-9 | | 5(2t+8)-6=10t+8 | | 76=4x+20 | | n-18=24 | | 13=f+3 | | 880+.09x=980 | | -4n+9=5-2(2n-6 | | -27+3x=x+29 | | 5/6x-11/20=1/6x-4/5 | | 7y-3y-5=63.48 | | x/5+x/8=14/40 | | -118+4x=-5x+80 | | 2x÷3=-5(x-8)-3 | | -1/2(x+2)11/2=3 | | 7(5x+3)=21-7x | | 28n+3=4n | | -(6y+3)-(-5-7)=-1 |